New Policies for New Residents : Immigrants, Advocacy, and Governance in Japan and Beyond - Milly, Deborah J., 1952- (Book collections on Project MUSE., 2014)
In recent decades, many countries have experienced both a rapid increase of in-migration of foreign nationals and a large-scale devolution of governance to the local level. The result has been new government policies to promote the social inclusion of recently arrived residents. In New Policies for New Residents, Deborah J. Milly focuses on the intersection of these trends in Japan. Despite the country's history of restrictive immigration policies, some Japanese favor a more accepting approach to immigrants. Policies supportive of foreign residents could help attract immigrants as the country adjusts to labor market conditions and a looming demographic crisis. As well, local citizen engagement is producing more inclusive approaches to community. Milly compares the policy discussions and outcomes in Japan with those in South Korea and in two similarly challenged Mediterranean nations, Italy and Spain. All four are recent countries of immigration, and all undertook major policy innovations for immigrants by the 2000s. In Japan and Spain, local NGO-local government collaboration has influenced national policy through the advocacy of local governments. South Korea and Italy included NGO advocates as policy actors and partners at the national level far earlier as they responded to new immigration, producing policy changes that fueled local networks of governance and advocacy. In all these cases, Milly finds, nongovernmental advocacy groups have the power to shape local governance and affect national policy, though in different way.